Study on the Relationships between Intrinsic Functional Connectivity of the Default Mode Network and Transient Epileptic Activity - Lopes, Renaud; Moeller, Friederike; Besson, Pierre; Ogez, François; Szurhaj, William; Leclerc, Xavier; Siniatchkin, Michael; Chipaux, Mathilde; Derambure, Philippe; Tyvaert, Louise (Frontiers in Neurology, 2014)
Rationale. Simultaneous recording of electroencephalogram and functional MRI (EEG-fMRI) is a powerful tool for localizing epileptic networks via the detection of hemodynamic changes correlated with interictal epileptic discharges (IEDs). FMRI can be used to study the long-lasting effect of epileptic activity by assessing stationary functional connectivity during the resting-state period (especially the connectivity of the default mode network (DMN)). Temporal lobe epilepsy (TLE) and idiopathic generalized epilepsy (IGE) are associated with low responsiveness and disruption of DMN activity. A dynamic functional connectivity approach might enable us to determine the effect of IEDs on DMN connectivity and to better understand the correlation between DMN connectivity changes and altered consciousness. Method. We studied dynamic changes in DMN intrinsic connectivity and their relation to IEDs. Six IGE patients (with generalized spike and slow waves) and 6 TLE patients (with unilateral left temporal spikes) were included. Functional connectivity before, during and after IEDs was estimated using a sliding window approach and compared with the baseline period. Results. No dependence on window size was observed. The baseline DMN connectivity was decreased in the left hemisphere (ipsilateral to the epileptic focus) in TLEs and was less strong but remained bilateral in IGEs. We observed an overall increase in DMN intrinsic connectivity prior to the onset of IEDs in both IGEs and TLEs. After IEDs in TLEs, we found that DMN connectivity increased before it returned to baseline values. Most of the DMN regions with increased connectivity before and after IEDs were lateralized to the left hemisphere in TLE (i.e., ipsilateral to the epileptic focus). Conclusion. Results suggest that DMN connectivity may facilitate IED generation and may be affected at the time of the IED. However, these results need to be confirmed in a larger independent cohort.